A Two-Case Series of Oral Candidiasis as an Opportunistic Infection in HIV Patients - Reshaina Dewi Azizah Zahratuljannah; Embun Khaerunnisa; Nanditya Maharani; Gede Perdana Putera; Heppy Oktavianto; Pratiwi Nur Widyaningsih (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2026)
Background: Oral candidiasis remains one of the most common opportunistic infections in people living with HIV (PLHIV), particularly in patients with impaired cellular immunity. Pseudomembranous candidiasis is clinically relevant because it may indicate immune deterioration, low CD4+ T-cell count, or advanced HIV disease. Case Presentation: This case series describes two HIV-positive male patients who presented with extensive pseudomembranous oral candidiasis. The first patient was a 30-year-old male with known HIV infection and concomitant Pneumocystis jirovecii pneumonia. Intraoral examination showed removable whitish-yellow plaques on the tongue, vestibular mucosa, and lips, with an erythematous base after removal. His CD4+ T-cell count was 258 cells/μL. Antiretroviral therapy was initiated during hospitalization, followed by antifungal treatment using nystatin oral drops, ketoconazole, and adjunctive antiseptic mouthwash. The second patient was a 35-year-old ART-naïve male with systemic symptoms and widespread removable pseudomembranous plaques involving the tongue, buccal mucosa, gingiva, and palate. His CD4+ T-cell count was 11 cells/μL, indicating profound immunosuppression. Conclusion: Pseudomembranous oral candidiasis may serve as an important clinical marker of CD4+ T-cell depletion and immune deterioration in PLHIV. Dentists should recognize this lesion early because oral findings may support timely referral, HIV disease assessment, and comprehensive management.